Development of cranberry extract films for the enhancement of food packaging antimicrobial properties. (June 2021) - Severo, Catarina; Anjos, Inês; Souza, Victor G.L.; Canejo, João P.; Bronze, M.R.; Fernando, Ana Luisa; Coelhoso, Isabel; Bettencourt, Ana F.; Ribeiro, Isabel A.C.
Graphical abstract: Highlights: Cranberry-chitosan films were prepared as active packaging materials. Cranberry extracts composition was successfully addressed by HPLC-MS/MS. E. coli and S. aureus biofilms were significantly reduced by cranberry films. The observed antioxidant activity can be added value to extend food shelf life. Abstract: The purpose of this study was to investigate the potential of cranberry extract as a valuable antibiofilm additive of chitosan-based films intended for food packaging applications. Two types of chitosan-based films differing in the plasticizers content (PEG alone or PEG and glycerol) were prepared by casting methodology. Cranberry-extracts were proven to be suitable for presenting antioxidant (i.e. DPPH scavenging ability) and antimicrobial activity (towards Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923). Additionally, among phenolic compounds present, responsible for those activities were isorhamnetin-3-glucoside, hydroxybenzoic acid, phloridzin, pelargonidin, chlorogenic acid, epicatechin and A-type procyanidin that were identified by HPLC-MS/MS. Films incorporating cranberry extracts showed adequate food preservation characteristics (light transmission, water and oxygen permeability). Produced films were also able to quench DPPH radical by 92.2 ± 3.9 (PEG added) and 89.7 ± 0.7 % (PEG and glycerol added) and inhibit E. coli and S. aureus biofilm formation. Concerning E. coli, a reduction of 5 and 4 log units was obtained with films added of PEG or PEG/glycerol, respectively. Remarkably, both chitosan-films completely prevented S. aureus biofilm. The obtained results place cranberry-chitosan films as a potential option for food packaging with antioxidant and antibiofilm properties as added value.